PENGARUH PERSEPSI HARGA, PERSEPSI MEREK, TERHADAP MINAT BELI ULANG DENGAN PERSEPSI NILAI SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pelanggan Bidadari Salon dan Spa Malang) - Dinda Ayuniar; N. Rachma; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTBidadari Salon and Spa is one of beauty and hair care service company inMalang City. Many service offered by Bidadari Salon is an affordable price, roomfor beauty care that is clean and comfortable. This study aims to determine theinfluence of price perceptions, brand perceptions, to re-buy interest with theperception of value as an intervening variable (case study on Bidadari Salon andSpa). Data were collected trough questionnaires and data were analyzed usingSPSS 16.0. Based on the result of the research can be seen that the perception ofprice affect the perception of value with significance of 0,498 (positive), andbrand perception does effect the perception of value with significance of 0,280(positive). Price perception has effect on repurchase interest with significantequal to 0,473, brand perception have an effect on to re-buy interest withsignificant equal to 0,280, perception of value does an effect to re-buy interestwith value significance that is equal to 0,990 . The perception of value is able tomediate the relationship between price perceptions of repurchase interest, and theperception of value is unable to mediate the relationship between brand’sperception of repeat interest.Keywords: Bidadari Salon and Spa, perception, significance, interveningvariable